Provision of Fluoride Varnish to Medicaid-Enrolled Children by Physicians: The Massachusetts Experience - Isong, Inyang A (Blackwell Science Inc, 2011)
OBJECTIVES: To evaluate the impact of a 2008 Medicaid policy in Massachusetts (MA), regarding reimbursing physicians for providing fluoride varnish (FV) to eligible children in medical settings. DATA SOURCE: Survey of a sample of primary care physicians in MA. STUDY DESIGN: Cross-sectional survey of a sample of physicians who provide care to MassHealth (MA Medicaid) enrolled-children. Dependent variables: history of completed preventive dental skills training, and FV provision. Independent variables: oral health knowledge, FV-attitudes, and physician and practice characteristics. PRINCIPAL FINDINGS: Overall, 19 percent of respondents had completed the training required to be eligible to bill for FV provision. Only 5 percent of physicians were providing FV. Most respondents (63 percent) were not familiar with the new policy, and only 25 percent felt that FV should be provided during well-child visits. Most physicians (60 percent) did not feel that the reimbursement rate of U.S.$26/application was sufficient; 17 percent said that they would not provide FV, regardless of payment. Most common barriers to FV provision were a lack of time and logistical challenges. CONCLUSIONS: Our findings suggest that simply reimbursing physicians for FV provision is insufficient to ensure provider participation. Success of this policy will likely require addressing several barriers identified.